First g-factor measurement using a radioactive $^{76}$Kr beam - Benczer-Koller, N.; Kumbartzki, G.; Cooper, J.R.; Mertzimekis, T. J.; Taylor, M.J.; Bernstein, L.; Hiles, K.; Maier-Komor, P.; McMahan, M.A.; Phair, L.; Powell, J.; Speidel, K.-H.; et al. (Eur. Phys. J. A, 2005)
The g factor of the first 2+1 state of radioactive 76Kr ( T 1/2 = 14.8 h) has been measured using projectile Coulomb excitation in inverse kinematics combined with the transient magnetic-field technique. The 76Kr beam was produced and accelerated in batch mode (re-cyclotron method) at the Lawrence Berkeley National Laboratory 88-Inch Cyclotron. The g factor g(76Kr; 2+1) = +0.37(11) was obtained. © Societa? Italiana di Fisica / Springer-Verlag 2005.